2020
DOI: 10.1002/jbm.a.37107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta‐tricalcium phosphate nanoparticles on the properties of a thermosensitive chitosan/collagen hydrogel and controlled release of quercetin

Abstract: In the present study, an inorganic matrix of beta‐tricalcium phosphate (bTCP) nanoparticles and quercetin was incorporated into an organic matrix of 2:1 (w/w) chitosan/collagen composite to fabricate thermosensitive bTCP‐chitosan/collagen‐quercetin hydrogels. A sol–gel transition of the hydrogels was stimulated by beta‐glycerophosphate (bGP) and temperature changes at physiological temperature and pH levels. Thereafter, the effects of 1%–3% (w/v) bTCP on properties of the bTCP‐bGP‐2:1 (w/w) chitosan/collagen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…All our testing results proved that CS-based scaffolds with 20% of BCP meet or exceed the minimum requirements of physicochemical performance for bone tissue engineering scaffolds. This phenomenon is attributed not only to the formation of a strong network penetration of BCP particles into the surface of CS networks but also to strong ionic interaction between PO 4 −3 in BCP with NH 3+ in CS [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…All our testing results proved that CS-based scaffolds with 20% of BCP meet or exceed the minimum requirements of physicochemical performance for bone tissue engineering scaffolds. This phenomenon is attributed not only to the formation of a strong network penetration of BCP particles into the surface of CS networks but also to strong ionic interaction between PO 4 −3 in BCP with NH 3+ in CS [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Defects in the filler may affect the application of the gel. It has been reported that the addition of tricalcium phosphate nanoparticles increases the mechanical strength while decreases the swelling and degradation rate, pore size, permeability, and quercetin release rate of the hydrogel [55]. For instance, as shown in Figure 3(c), a series of hybrid graphene oxide (GO)/PVA composite hydrogels have been reported with different potential applications in artificial cartilage and tissue engineering [56,57].…”
Section: Filler Reinforcementmentioning
confidence: 99%
“…When a hydrogel is employed as the carrier for the local administration of Que, the key issue concerned is how to efficiently load enough amount of Que into the hydrogel and manage its controlled and sustained release. Direct loading of Que into hydrogels with the aid of organic solvents such as ethanol and dimethyl sulfoxide has been explored [ 33 , 36 , 53 ]. In doing so, the organic solvent should be removed from the resulting hydrogels otherwise such Que-loaded hydrogels may cause potential side effects due to the solvent release; in addition, this kind of Que-loaded hydrogel usually shows a severe initial burst because in many cases, hydrogels constructed with natural polymers have limited ability to administer the controlled and sustained release of drugs or biomolecules [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin (Que) is a kind of naturally sourced flavonoid compound and it shows a wide spectrum of biological activities [ 31 , 32 ], including antioxidation, anti-inflammation, anti-hypertension, anti-carcinogenicity, immunomodulatory actions, and so on. Que has also been used for bone repair due to its functions for promoting osteogenesis, anti-oxidation, anti-inflammation, and so on [ 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%